THE USE OF RICE WASHING WATER FERMENTATION SOLUTION AND VINEGAR ON THE SHELF LIFE OF RED TILE FILET BASED ON THE NUMBER OF MICROBES IN LOW TEMPERATURE STORAGE - Luther, Abraham; Liviawaty, Evi; Haetami, Kiki (Universitas Mataram, 2025)
Tilapia fillets are very susceptible to quality degradation. Therefore, efforts need to be made to maintain the quality of tilapia fillets with preservation methods using natural materials such as rice washing water waste. Rice washing water added with vinegar can grow lactic acid bacteria (LAB) through a fermentation process where LAB can fight spoilage bacteria in processed fishery products. The purpose of this study was to determine the use of optimal vinegar concentration in rice washing water fermentation solution to extend the shelf life of tilapia fillets based on the number of bacteria and pH during low temperature storage. The research method used in this study is a descriptive method. The treatment used was the addition of 0%, 0.5%, 1%, 1.5%, 2% vinegar solution and stored at low temperatures (5°-10). The parameters measured included the number of bacterial colonies and the degree of acidity (pH). Concentration 0% observations were made on days 1, 3, 6, 7, 8, 9 while for concentrations of 0.5%, 1%, 1.5%, 2% observations were made on days 1, 4, 7, 8, 9, 10, 11, and 12. The results showed that the fermentation solution of rice washing water with the addition of 1% vinegar concentration was the best for extending shelf life. The treatment of 1% vinegar concentration can maintain the quality of red tilapia fillets until the 11th day with a total of 5.6×107 bacteria and a pH value of 6.70.